Myeloperoxidase/HLA Class II Complexes Recognized by Autoantibodies in Microscopic Polyangiitis. Issue 10 (25th August 2017) - Hiwa, Ryosuke; Ohmura, Koichiro; Arase, Noriko; Jin, Hui; Hirayasu, Kouyuki; Kohyama, Masako; Suenaga, Tadahiro; Saito, Fumiji; Terao, Chikashi; Atsumi, Tatsuya; Iwatani, Hirotsugu; Mimori, Tsuneyo; et al.
Abstract : Objective: Autoantibodies against myeloperoxidase (MPO) that are expressed in neutrophils play an important role in the pathogenesis of microscopic polyangiitis (MPA). We recently observed that misfolded cellular proteins are transported to the cell surface by HLA class II molecules and are targeted by autoantibodies in patients with rheumatoid arthritis or antiphospholipid syndrome, suggesting that HLA class II molecules play an important role in autoantibody recognition. The aim of this study was to address the role of HLA class II molecules in the cell surface expression of MPO in patients with MPA. Methods: The association of MPO with HLA–DR was analyzed using MPO and HLA–DR transfectants as well as neutrophils from healthy donors and patients with MPA. Autoantibody binding to the MPO/HLA–DR complex was analyzed by flow cytometry. The association of MPO with HLA–DR was assessed using the immunoprecipitation technique. The function of MPO–antineutrophil cytoplasmic antibody (ANCA) was assessed using a neutrophil‐like cell line expressing HLA–DR and MPO. Results: MPO protein was detected on the cell surface in the presence of HLA–DR, and the MPO/HLA–DR complex was recognized by MPO‐ANCA. A competitive inhibition assay suggested that MPO associated with HLA–DR expresses cryptic autoantibody epitopes for MPO‐ANCA. Autoantibody binding to the MPO/HLA–DR complex was correlated with disease susceptibility conferred by each HLA–DR allele, suggesting that the MPO/HLA–DR complex is involved in the pathogenicity of MPA. Indeed, MPO–HLA class II complexes were detected in neutrophils from a patient with MPA as well as in cytokine‐stimulated neutrophils from healthy donors. Moreover, MPO‐ANCA stimulated MPO/HLA–DR complex–expressing HL‐60 cells. Conclusion: Our findings suggest that MPO complexed with HLA class II molecules is involved in the pathogenesis of MPA as a target for MPO‐ANCA.